Problematika Pertimbangan Hukum Hakim Dalam Putusan MK Nomor 66/PUU-XXIV/2026 Terkait Kerugian Keuangan Negara Dalam Hukum Administrasi Negara - Reva Aurelia Azzah; Ahnaf Daffa Fakhruddin Madjid; Muh. Ali Masnun (NOVUM : JURNAL HUKUM, 2026)
This research focuses on the legal considerations of judges in the Constitutional Court Decision Number 66/PUU-XXIV/2026 regarding the interpretation of state financial losses from the perspective of Administrative Law. The research problem arises from the conceptual differences between state financial losses in criminal law, which emphasize tangible, actual, and financially calculable losses, and the concept of state financial losses in Administrative Law, which has a broader scope. This research uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach thru the analysis of Constitutional Court Decision Number 66/PUU-XXIV/2026. The research results show that the Constitutional Court maintains the use of the term "state financial loss" in the Government Administration Law on the grounds that it provides a clearer, more objective, and measurable measure of loss, thereby ensuring legal certainty. However, the legal considerations are not yet fully relevant to the concept of state financial loss in Administrative Law because they are still dominated by a criminal law approach that is oriented toward economic and financial losses. However, in Administrative Law, state financial losses do not only encompass technical, economic, and factual losses, but also include administrative, institutional, and functional losses such as disruptions in public services, procedurally flawed decisions, abuse of authority, declining public trust, and failure to achieve government objectives. The legal implication of that decision is the narrowing of the meaning of state financial loss, which has the potential to create legal uncertainty in government administrative practices. Therefore, constitutional judges need to integrate juridical, philosophical, and sociological approaches more balancedly and pay attention to the principles of good governance and the General Principles of Good Governance (AUPB), while further research should develop multidisciplinary studies to clarify the conceptual boundaries of state financial losses in various legal regimes